PENDAMPINGAN WATER QUALITY MANAGEMENT KELOMPOK PEMBUDIDAYA IKAN SIPODALLE’ KECAMATAN TINAMBUNG SEBAGAI UPAYA PENINGKATAN PRODUKTIVITAS TAMBAK SULAWESI BARAT - Nasyrah, Adiara Firdhita Alam; Nur, Fauzia; Mahfud, Chairul Rusyd; Noor, Rahmat Januar; Nur, Muhammad (Jurnal Abdi Insani, 2024)
Coastal communities in Tinambung Subdistrict, West Sulawesi utilize the potential of traditional aquaculture in their area. POKDAKAN Sipodalle is one of the traditional aquaculture systems with a polyculture method between milkfish and vanamei shrimp. However, the constraints faced are declining production yields as a result of crop failure due to commodities attacked by pests and diseases. One of the crucial things that need to be considered is water quality. The purpose of the activity is to increase knowledge for the Sipodalle' Fish Cultivation Group (POKDAKAN) about traditional pond water quality. The availability of water quality measurement tools managed by partners to increase productive cultivation. The activity was held on Monday, June 22, 2024 at the Tandung Village Office Hall, Tinambung District, West Sulawesi Province. The main participants of this service were Sipodalle' POKDAKAN, but also involved students and lecturers. The method applied was training using presentation methods and hands-on practice on how to use water quality checking tools. The results of the service activities showed an increase in farmers' knowledge related to traditional pond water quality management, techniques and SOPs for checking pond water quality. Furthermore, from this activity, the group of farmers obtained water quality checking tools and farmers already know how to use these tools. The results of the training opened the insight of farmers to pay attention to shrimp health through water quality control from water quality measurement tools provided including DO meters, pH meters, and thermometers. The end result is that farmers can monitor water quality to prevent pond water problems including optimizing growth and better yields. The community service activities carried out have been carried out smoothly and well. Partner problems related to lack of knowledge about water quality are overcome through understanding water quality parameters effectively.